2021
DOI: 10.1017/s0144686x21001525
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of influencing one's own life when living with working-age dementia

Abstract: Having opportunities to make decisions and choices regarding one's life is crucial when living with dementia. This inter-disciplinary study draws on the concept of relational autonomy to explore how working-age people living dementia seek to influence their lives, and what makes it easier or more difficult for them in their everyday life. The data consist of three focus group discussions conducted with 12 retired adults who developed dementia while still employed. The results illuminate various resources that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Ritchie et al ( 2018 ) concluded that employees with dementia have little control over decisions made regarding their employment, as was also shown in a recent study by our research team (Issakainen et al, 2021 ). When the medical expertise set the diagnosis, the participants in this study were told to leave work—again reflecting the power of dementia stereotypes of immediate incapacity (Low & Purwaningrum, 2020 ) - even if this recommendation was not always financially supported by the SSIA.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Ritchie et al ( 2018 ) concluded that employees with dementia have little control over decisions made regarding their employment, as was also shown in a recent study by our research team (Issakainen et al, 2021 ). When the medical expertise set the diagnosis, the participants in this study were told to leave work—again reflecting the power of dementia stereotypes of immediate incapacity (Low & Purwaningrum, 2020 ) - even if this recommendation was not always financially supported by the SSIA.…”
Section: Discussionsupporting
confidence: 66%
“…For someone who develops dementia, continued employment is likely to require adjustments or accommodations at work, which can be difficult to support (Ritchie et al, 2018 ; Roach & Drummon, 2014 ; Stavert et al, 2018 ; Öhman et al, 2001 ). To facilitate continued employment, a person-centred approach, including collaboration, guidance, and training for employers on legal and human rights, has been suggested (Andrew et al, 2018 ; Issakainen et al, 2021 ; Ritchie et al, 2018 ; Stavert et al, 2018 ). Specifically, the process of making adjustments, e.g., changing work schedules, simplifying routines, using technology for reminders, has been identified as a key theme requiring urgent attention (Thomson et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier research has documented the challenges faced in managing work and the tendency of early retirement when a person develops dementia while still employed (e.g. Evans, 2019; Issakainen et al, 2021; Ritchie et al, 2018). Several studies address the lack of support and understanding of reasonable accommodations that narrow down opportunities available for people living with dementia or mild cognitive impairment (e.g.…”
Section: Introductionmentioning
confidence: 99%